2008
DOI: 10.1016/j.actamat.2008.04.055
|View full text |Cite
|
Sign up to set email alerts
|

A three-phase simulation of the effect of microstructural features on semi-solid tensile deformation

Abstract: A direct finite element microstructure model for prediction of the deformation behavior of semisolid metallic alloys is presented. The 2D model geometry is based on a modified Voronoi tessellation, and includes rounded corners to approximate an equiaxed-globular grain structure, liquid surrounding the grains, and micro porosity. An elasto-plastic empirical constitutive equation is derived for the solid grains, while the liquid is approximated as a perfectly plastic material with a very low yield stress. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 35 publications
0
48
0
Order By: Relevance
“…Hence, although the behavior of the solid grains is actually elastic-perfectly plastic, the behavior of the entire semisolid material is not, as is shown in Figure 4. Instead, it undergoes geometric strain hardening [19] during deformation. An initial stress increase can also be observed in the results for g s = 0.94 and g s = 0.98.…”
Section: B Tensile Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, although the behavior of the solid grains is actually elastic-perfectly plastic, the behavior of the entire semisolid material is not, as is shown in Figure 4. Instead, it undergoes geometric strain hardening [19] during deformation. An initial stress increase can also be observed in the results for g s = 0.94 and g s = 0.98.…”
Section: B Tensile Deformationmentioning
confidence: 99%
“…Generation of this geometry requires a methodology for simulating the solidification of numerous grains. Previous work by the authors [15][16][17][18][19]33] has resulted in the development of a 3D granular solidification model known as GMS-3D, [31] which is able to generate the required solid-liquid two-phase geometry at a fixed g s . In this model, the grain structure is derived from a Voronoi tessellation of random nucleation centers.…”
Section: A Generation Of Discrete Elements Using a Solidification Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample behaviour can then be studied with respect to various parameters. For instance, by using a modified Voronoi tessellation, Phillion et al showed the effect of microstructural features on the semi-solid tensile deformation of an aluminium alloy such as solid fraction, porosity and grain size [1].…”
Section: Introductionmentioning
confidence: 99%
“…The sample behaviour can then be studied with respect to various parameters. For instance, by using a modified Voronoi tessellation, Phillion et al showed the effect of microstructural features on the semi-solid tensile deformation of an aluminium alloy such as solid fraction, porosity and grain size [1].During the last decade, X-ray microtomography has considerably developed [2][3][4]. This imaging technique gives access to in situ three-dimensional (3D) morphology of a multiphase sample.…”
mentioning
confidence: 99%